إمكانية تطبيق المشاركة المتناقصة في التمويل العقاري في هونغ ليونغ إسلاميك بنك = The possibility of implementing Mushārakah Mutanāqiṣah contract in home financing at Hong Leong Islamic Bank - Zulqarnain, Aisyah Humairah; Zakariyah, Luqman (IIUM Press, International Islamic University Malaysia, 2019)
Mushārakah Mutanāqiṣah (MM) or Diminishing Partnership is one of the financing contracts that comply with Shariah and many Malaysian Islamic banks have introduced this mode of contract into their home financing product except Hong Leong Islamic Bank and some other Islamic banks who have not yet done so. Thus, this research intends to study the possibility of offering MM contract in Islamic Home Financing as a product at Hong Leong Islamic Bank. The researchers conducted a field study through several interviews with the staff working in the product development department and department of Shariah in some of the Malaysian Islamic banks. From the theoretical aspect, the researchers explain the concept of home financing, MM and the fiqh perspective of the subject in question. The responses received during the interviews are used to analyze the possibility of offering MM contract in Islamic Home Financing product at Hong Leong Islamic Bank. This research concludes that there is a possibility for Hong Leong Islamic Bank to do so, should it consider some suggestions presented in this paper.